Implementation of Active, Creative and Fun Learning (PAKEM) and Motivation in Improving Student Learning Outcomes - Imam Santoso; Winner Saragih (Eduvest - Journal of Universal Studies, 2021)
The purpose of this study was to determine the effect of PAKEM (active, creative and fun learning) and learning motivation on student learning outcomes in science subjects at 31 State Junior High Schools in Tangerang City. This study uses a quantitative approach, descriptive and associative types. The population in this study was 554 students. The sampling technique used in this study is the Slovin formula. By using the slovin formula technique, a sample of 41 students of 31 Tangerang City Junior High School was taken as respondents in this study. The results of this study indicate that: 1) the tcount value for X1 (Active, Creative and Fun Learning)) is 5,831 while the ttable value for n = 41 is 2,020. So 5,831 > 2,020, Can Key partially affect student learning outcomes. 2) the t-count value for the X2 variable (Learning Motivation) is 3.399, while the ttable value for n = 41 is 2,020. So 3.399 > 2.020, the key can be partially that Learning Motivation has an effect on Student Learning Outcomes. 3) ANOVA test or Ftest or Fcount obtained a value of 39.815 which is greater than Ftable of 2.83 or 39.815 > 2.83 with a significant level of 0.000 because 0.000 <0.05, it can be said that the Pakem variable (Active, Creative and Fun Learning) (X1) and the variable of Learning Motivation (X2) together have an effect on the variable of Student Learning Outcomes (Y).